Association of Hypertension With Both Occurrence and Outcome of Symptomatic Patients With Mild Intracranial Atherosclerotic Stenosis: A Prospective Higher Resolution Magnetic Resonance Imaging Study. Issue 1 (10th March 2021) - Shi, Zhang; Zhao, Ming; Li, Jing; Meddings, Zakaria; Shi, Yibing; Jiang, Tao; Liu, Qi; Deng, Benqiang; Lu, Jianping; Teng, Zhongzhao
Abstract : Background: Intracranial atherosclerotic plaque causing mild luminal stenosis might lead to acute ischemic events. However, the difference between culprit and nonculprit lesions is unclear, as are the factors associated with favorable treatment outcomes. Purpose: To quantify characteristics of intracranial atherosclerosis with mild luminal stenosis and to identify factors associated with lesion type (culprit or nonculprit) and with clinical outcomes. Study Type: Prospective Population: 293 patients who had acute stroke with mild luminal stenosis (<50%) in the middle cerebral or basilar artery. Field Strength/Sequence: 3.0 T higher resolution magnetic resonance imaging (hrMRI) of intracranial arteries and whole brain MR images. Assessment: Morphological and compositional analysis of plaques was performed. This included assessment of plaque volume, plaque burden, remodeling ratio, eccentricity, intraplaque hemorrhage, and enhancement ratio. Clinical outcomes were assessed according to the modified Rankin Scale (mRS) at day 90, with a favorable outcome being defined as a 90‐day mRS ≤2. Statistical Tests: The odds ratios (ORs) with 95% confidence intervals (CIs) were calculated by a logistic regression model. Results: Hypertension (OR 5.2; 95% CI 2.6–10.3; P < 0.05) and hrMRI enhancement ratio (OR 2.7; 95% CI 1.4–5.1; P < 0.05) were independently associated with lesion type. Patients without hypertension had significantly more ( P < 0.05) favorable outcomes (124/144) than patients with hypertension (97/149). Most hypertensive patients without any previous blood pressure control (54/63) had a favorable outcome. However, these patients were significantly younger ( P < 0.05) than those with adequate blood pressure control. After adjusting for all significant characteristics, hypertension duration (OR 1.19; 95% CI 1.09–1.29; P < 0.05), hypertension management (OR 2.49; 95% CI 1.18–5.26; P < 0.05), and enhancement ratio (OR 0.01; 95% CI 0.001–0.157; P < 0.05) were found to be independent high‐risk factors for outcome prediction. Data Conclusion: hrMRI provided incremental value over traditional risk factors in identifying higher risk intracranial atherosclerosis with mild luminal stenosis. Level of Evidence: 2 Technical Efficacy: Stage 2